Effects of dexmedetomidine in conjunction with remote ischemic preconditioning on renal ischemia–reperfusion injury in rats - Bagcik,Emine (2014)
Background and objectives: The aim of this study was to evaluate the effects of remote ischemic preconditioning by brief ischemia of unilateral hind limb when combined with dexmedetomidine on renal ischemia-reperfusion injury by histopathology and active caspase-3 immunoreactivity in rats. Methods: 28 Wistar albino male rats were divided into 4 groups. Group I (Sham, n = 7): Laparotomy and renal pedicle dissection were performed at 65th minute of anesthesia and the rats were observed under anesthesia for 130min. Group II (ischemia-reperfusion, n = 7): At 65th minute of anesthesia bilateral renal pedicles were clamped. After 60 min ischemia 24 h of reperfusion was performed. Group III (ischemia-reperfusion + dexmedetomidine, n = 7): At the fifth minute of reperfusion (100 μg/kg intra-peritoneal) dexmedetomidine was administered with ischemia-reperfusion group. Reperfusion lasted 24 h. Group IV (ischemia-reperfusion + remote ischemic preconditioning + dexmedetomidine, n = 7): After laparotomy, three cycles of ischemic preconditioning (10 min ischemia and 10 min reperfusion) were applied to the left hind limb and after 5 min with group III. Results: Histopathological injury scores and active caspase-3 immunoreactivity were significantly lower in the Sham group compared to the other groups. Histopathological injury scores in groups III and IV were significantly lower than group II (p = 0.03 and p = 0.05). Active caspase-3 immunoreactivity was significantly lower in the group IV than group II (p = 0.01) and there was no significant difference between group II and group III (p = 0.06). Conclusions: Pharmacologic conditioning with dexmedetomidine and remote ischemic preconditioning when combined with dexmedetomidine significantly decreases renal ischemia- reperfusion injury histomorphologically. Combined use of two methods prevents apoptosis via active caspase-3.